Lionessheart: A Screenplay of Firstborn Daughter’s Struggles in Family and Society - Sharon Valery Suwanto (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
Eldest Daughter Syndrome, more commonly recognized as Child Parentification of the firstborn daughter, describes the phenomenon of parents burdening family responsibilities to their firstborn daughter. Child parentification is common in Asian families including Indonesian families, where parents tend to have an authoritarian parenting style that emphasizes strictness, harshness, and the expectation of obedience from their children (Ang & Goh, 2006). Using Gregor Jurkovic’s theory of “Lost Childhood,” this creative work will highlight the difficulties of being a parentified child, its impacts on their psyche, and potential solutions. It will also explore how individuals can deal with their trauma by seeking support and empowerment from their socioemotional environment. The screenplay portrays the parentified character struggles with anger and resentment towards her parents, stress, and identity disruption. The main impact of these struggles is deep trauma, which is addressed through empowerment and support in her socioemotional growth from her friends.